Aboriginal Women's Experiences With Gestational Diabetes Mellitus: A Participatory Study With Mi'kmaq Women in Canada. (April 2016) - Whitty-Rogers, Joanne; Caine, Vera; Cameron, Brenda
Abstract : In Canada, diabetes is 3 to 5 times more common among Aboriginal people than in the general population. Women with a diagnosis of gestational diabetes mellitus have an increased risk of developing glucose intolerance later in life, with almost half developing type II diabetes within 15 years. A participatory action research study using a Two-Eyed Seeing approach was conducted. Conversational interviews with 9 Mi'kmaq women who experienced gestational diabetes mellitus and talking circles were held. Hermeneutic phenomenology was used for data analysis. Themes included life-altering experience; barriers limiting access to health care; social support during pregnancy; and feeling compelled to take action.